First-Line Catheter Ablation of Monomorphic Ventricular Tachycardia in Cardiomyopathy Concurrent With Defibrillator Implantation: The PAUSE-SCD Randomized Trial. Issue 25 (4th May 2022) - Tung, Roderick; Xue, Yumei; Chen, Minglong; Jiang, Chenyang; Shatz, Dalise Y.; Besser, Stephanie A.; Hu, Hongde; Chung, Fa-Po; Nakahara, Shiro; Kim, Young-Hoon; Satomi, Kazuhiro; Shen, Lishui; et al.
Abstract : Background: Catheter ablation as first-line therapy for ventricular tachycardia (VT) at the time of implantable cardioverter defibrillator (ICD) implantation has not been adopted into clinical guidelines. Also, there is an unmet clinical need to prospectively examine the role of VT ablation in patients with nonischemic cardiomyopathy, an increasingly prevalent population that is referred for advanced therapies globally. Methods: We conducted an international, multicenter, randomized controlled trial enrolling 180 patients with cardiomyopathy and monomorphic VT with an indication for ICD implantation to assess the role of early, first-line ablation therapy. A total of 121 patients were randomly assigned (1:1) to ablation plus an ICD versus conventional medical therapy plus an ICD. Patients who refused ICD (n=47) were followed in a prospective registry after stand-alone ablation treatment. The primary outcome was a composite end point of VT recurrence, cardiovascular hospitalization, or death. Results: Randomly assigned patients had a mean age of 55 years (interquartile range, 46–64) and left ventricular ejection fraction of 40% (interquartile range, 30%–49%); 81% were male. The underlying heart disease was ischemic cardiomyopathy in 35%, nonischemic cardiomyopathy in 30%, and arrhythmogenic cardiomyopathy in 35%. Ablation was performed a median of 2 days before ICD implantation (interquartile range, 5 days before to 14 days after). At 31 months, the primary outcome occurred in 49.3% of the ablation group and 65.5% in the control group (hazard ratio, 0.58 [95% CI, 0.35–0.96]; P =0.04). The observed difference was driven by a reduction in VT recurrence in the ablation arm (hazard ratio, 0.51 [95%CI, 0.29–0.90]; P =0.02). A statistically significant reduction in both ICD shocks (10.0% versus 24.6%; P =0.03) and antitachycardia pacing (16.2% versus 32.8%; P =0.04) was observed in patients who underwent ablation compared with control. No differences in cardiovascular hospitalization (32.0% versus. 33.7%; hazard ratio, 0.82 [95% CI, 0.43–1.56]; P =0.55) or mortality (8.9% versus 8.8%; hazard ratio, 1.40 [95% CI, 0.38–5.22]; P =0.62]) were observed. Ablation-related complications occurred in 8.3% of patients. Conclusions: Among patients with cardiomyopathy of varied causes, early catheter ablation performed at the time of ICD implantation significantly reduced the composite primary outcome of VT recurrence, cardiovascular hospitalization, or death. These findings were driven by a reduction in ICD therapies. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02848781.